2019
DOI: 10.1080/16878507.2019.1594136
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic profile activities of ethanolic and methanolic extracts of chicory plant (Cichorium intybus L.)

Abstract: View related articles View Crossmark data Cytotoxic profile activities of ethanolic and methanolic extracts of chicory plant (Cichorium intybus L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Both phenolic acids and flavonoids are known as antioxidant compounds, but their ability depends not only on the quantities but on the chemical structure also [ 52 ]. The DPPH radical scavenging activity of the extracts was modest (164.98 ± 5.93 µg/mL for the CHME and 336.35 ± 11.77 µg/mL for the CHT), but in accordance with other data [ 53 ]. Previous studies have reported even higher values (over 700 µg/mL), while several authors have obtained a better antioxidant activity for the hydroalcoholic extract of chicory leaves [ 54 ].…”
Section: Resultssupporting
confidence: 89%
“…Both phenolic acids and flavonoids are known as antioxidant compounds, but their ability depends not only on the quantities but on the chemical structure also [ 52 ]. The DPPH radical scavenging activity of the extracts was modest (164.98 ± 5.93 µg/mL for the CHME and 336.35 ± 11.77 µg/mL for the CHT), but in accordance with other data [ 53 ]. Previous studies have reported even higher values (over 700 µg/mL), while several authors have obtained a better antioxidant activity for the hydroalcoholic extract of chicory leaves [ 54 ].…”
Section: Resultssupporting
confidence: 89%
“…A good correlation was observed between total phenolic content and antioxidant activity. It is observed from the results of this study that the highest phenolic and flavonoid content of chicory extracts exhibited high antioxidant activities (Kandil et al,2019). The higher DPPH antioxidant activity in methanolic extract of Cichorium intybus L. is significantly higher than that of other solvents (p >0.05).…”
Section: Antioxidant Activity By Dpphmentioning
confidence: 61%
“…Eray et al,(2020) reported total flavonoid content in herbal parts of Cichorium intybus L.water extract range about 388.3±5.77 μg CE/mg, and methanolic extract range about 550±14.53 μg CE/mg. Also, our results were the lowest of these studies.On the other hand, Kandil et al,(2019) reported that the total flavonoid content of Cichorium intybus L. in methanolic extract range about 167.47 ± 5.83 μg QE/g,whiles in ethanolic extract range about 36.56 ± 5.95 μg QE/g.Our results were the higher of these studies.Also,the assessment flavonoid in EtOAc extracts does not have any previously publication results (EtOAc=No).…”
Section: Total Flavonoids Contentmentioning
confidence: 98%
See 1 more Smart Citation
“…C. intybus has been assessed as an in vitro antiproliferative activity against prostate cancer (LNCaP), amelanotic melanoma (C32), and renal adenocarcinoma (ACHN) cell lines (Mohammad et al, 2014). Additionally, crude methanolic extract of chicory exerted a potent cytotoxic activity (90%) against MCF-7 and AML-7 cell lines at 500 µg/mL (Kandil et al, 2019).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%